Langerhans cell histiocytosis of the mandible - A rare case report - Vennila Parameswaran; Sidra Bano (Wolters Kluwer Medknow Publications, 2020)
Langerhans cell histiocytosis (LCH) is a rare idiopathic disease that is characterized by the clonal proliferation of bone marrow-derived Langerhans cells. It usually occurs in children at an incidence of 2.6-5.4/10,00,000 children/year. The disease occurs with a slight male predilection. The peak age ranges from 1 to 4 years. The common oral findings include the gingival enlargement, oral ulcers, and loosening of teeth. The variable radiographic appearance mimicking odontogenic cyst, osteomyelitis, or a malignancy poses a diagnostic challenge. This rare case report emphasizes on the differential diagnosis of LCH.